FAKE NEWS AS A TOOL OF MEDIA INFLUENCE ON YOUNG PEOPLE: ON THE QUESTION OF DEFINITION AND CLASSIFICATION - A. A. Malkevich (Современная наука и инновации, 2022)
The article is devoted to the analysis of fake news as a phenomenon of modern mass communications and a tool of manipulative influence on the youth audience. The article offers the author's definition of the term "fake news", considers the key approaches to the definition and classification of this concept.